The Unity of Virtue and Body: Moral Realization in Mencius’ Theory of Embodying Virtue - Jiang, Siyuan; Liu, Pinghua (Religions (Basel, Switzerland ), 2025)
Mencius’ “Theory of Embodying Virtue 踐形說” is an important theory that combines moral cultivation and physical practice, emphasizing that virtue is externalized and realized through concrete physical actions. This paper explores the theoretical foundation of the “Theory of Embodying Virtue 踐形說”, examining its internal connections with Mencius’ doctrines of “Innate Goodness”, “Four Beginnings 四端”, and “Nurturing Qi 養氣”. Through self-cultivation, individuals can gradually transform their inner virtues into outward behaviors, ultimately achieving the unity of virtue and the body. This not only serves as an essential path for personal moral cultivation but also embodies the Confucian moral ideal. Additionally, the paper analyzes the contemporary significance of the “Theory of Embodying Virtue” from the perspectives of modern ethics and body philosophy, particularly in terms of its implications for moral education, the improvement of social ethics, and the shaping of leaders’ moral images. By conducting an in-depth discussion, this paper reveals that Mencius’ “Theory of Embodying Virtue” still holds significant theoretical and practical value in contemporary society.